Kolaborasi Industri Kreatif dalam Mendukung Pemulihan Pariwisata Indonesia Pasca Pandemi Covid-19 - Nusaybah Afaf Ashilah (Social Science Academic, 2026)
The COVID-19 pandemic has had a significant impact on Indonesia's tourism sector, which has long been one of the country's major sources of foreign exchange earnings. Restrictions on public mobility led to a substantial decline in tourist arrivals, hotel occupancy rates, and the overall activities of tourism-related businesses. In the post-pandemic era, the Indonesian government, together with various stakeholders, has undertaken efforts to revitalize the tourism sector by promoting high-quality and sustainable tourism development. One strategy considered to have considerable potential is the collaboration between the tourism sector and the creative industry. This article aims to analyze the role of the creative industry in supporting the recovery of Indonesia's tourism sector through a conceptual study approach. The research employs a literature review methodology by analyzing a wide range of scholarly publications, government documents, and statistical data related to the development of tourism and the creative economy in Indonesia. The findings indicate that the creative industry enhances the competitiveness of tourism destinations through product innovation, the adoption of digital technologies, strengthened destination branding, and the effective use of social media as a promotional platform. Furthermore, changes in tourist behavior following the pandemic have accelerated the emergence of experience-based tourism, hidden gem destinations, staycations, workcations, and sustainable tourism, further reinforcing the interconnection between the tourism sector and the creative economy. Therefore, cross-sector collaboration has become a key strategy for developing an adaptive, innovative, and sustainable tourism industry in Indonesia.